FAKTOR YANG MEMPENGARUHI MOTIVASI PESERTA DIDIK DALAM MENGIKUTI KEGIATAN EKSTRAKURIKULER DI SMP NEGERI 2 KOTO XI TARUSAN - Pratiwi, Chici - (Bimbingan dan Konseling, 2014)
This research is motivated by the presence of factors that influence the motivation oflearners in the following extracurricular activities. Based on the interview, that there are studentswho have problems in the following extracurricular activities, such as the learners who less thedesire to take advantage of extracurricular activities, the presence of the students less the motivationto participate in extracurricular activities and their learners who choose hang out with friends of thefollowing the extracurricular activities at school. The aimed of this research are to determine theintrinsic and extrinsic factors that influence the motivation of learners in the followingextracurricular activities This research is descriptive quantitative the population of all students in theJunior High School 2 Koto XI Tarusan. In this research, the sample amounted to 80people consistingof VII.4 class (25 people), VIII.5 (24 people) and IX.3 (31 people). The technique used in sampling isstratified random sampling. The instrument used in this study is a questionnaire, while the formulaused for data analysis and technical analysis criterion percentage. The results of this study revealedthat: 1) Intrinsic factors that influence the motivation of learners in the following extracurricularactivities consisting of the needs, expectations and interests were in many categories. 2) Extrinsicfactors that affect the motivation of learners in the following extracurricular activities consisting ofthe environment and the rewards are in the many categories. So, based on the results of research thatthe students in the following extracurricular activities in SMP Negeri 2 Koto XI Tarusan manyfactors that influence learner motivation, good views of the intrinsic and extrinsic factors inparticipating in extracurricular activities.